ANALYSING ENVIRONMENTAL IMPLICATIONS OF ANTHROPOGENIC IMPACTS AS A RESULT OF SYZRAN SHALE-PROCESSING REFINERY WORK (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Extraction and primary processing of natural minerals have a direct human impact on the lithosphere in the following way: the area of excavation and the area covered by rock dumps of overburden and substandard rocks increase; the landscape also changes. This problem occurs on all operated deposits and exists in out-of-operation deposits. This paper performs a critical analysis of environmental implications of anthropogenic impacts as a result of Syzran shale-processing refinery work Rock dumps parameters № 1 of Mine 3 and № 2 of Mine 5/6 of ZAO "Kashpirskaya Mine" are investigated. Rock dumps depth and surface ares, conservation volume and utilization capacity are considered to be landscape modifying parametres. The research demonstrates rock dumps parameters change in the period from 1950 to 2002. The paper evaluates the degree of anthropogenic impact of dumps territories and burnt rocks burials which were formed during the extraction of oil shale at Syzran shale-processing refinery. Those rock dumps resulted in the following transformation and change of the natural system and landscape: curvature of the slopes altered, soil and vegetation cover was dislocated. The only industry capable of reducing ecological tension in the region is building industry.